Cotton sector: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
At the global level the cotton market is dominated by the USA (the world’s biggest exporter) and China (63% of world’s stocks), while ACP countries account for just 5% of global production. However, cotton remains of considerable social and economic importance in the main ACP cotton producing countries – especially in West Africa. With higher production levels than consumption, in 2012/13 global cotton stocks grew for the third year in a row. However, prices showed less volatility than in previous years (there was a tremendous price spike in 2010/11), thanks, in particular, to Chinese support policies that stabilized global prices. This Executive Brief, after analyzing the main trends in the global cotton economy in 2012/13 and the production trends in the ACP, focuses on policy developments in the USA (the Farm Bill reform), the EU (CAP reform) and China, and the implication of cotton sector subsidies for African producers. Finally, attention is paid to the challenges that African producers still have to address in order to take advantage of the growing consumer demand for organic and fair trade cotton.